2012
DOI: 10.1016/j.vetpar.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oil-based formulations of acaripathogenic fungi to control Rhipicephalus microplus ticks under laboratory conditions

Abstract: The formulations of acaripathogenic fungi to control ticks have been widely studied. The present study evaluated the efficacy of oil-based formulations of Metarhizium anisopliae sensu lato (s.l.), isolate Ma 959, and Beauveria bassiana, isolate Bb 986, on different Rhipicephalus microplus stages, comparing the efficacy between aqueous suspensions and 10, 15 and 20% mineral oil formulations. Twelve groups were formed: one aqueous control group; three mineral oil control groups, at 10, 15 or 20%; two aqueous fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 21 publications
3
28
1
3
Order By: Relevance
“…Mineral and vegetable oils are used in formulations as adjuvants to protect conidia and to maximise fungal performance . Extensive research showed that oil formulations are more efficacious than aqueous formulations or wettable powders under various temperature and moisture conditions . In our experiment, compared with wettable powders, oil‐based formulations of I. fumosorosea were more effective against P. xylostella at the same conidial concentrations.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Mineral and vegetable oils are used in formulations as adjuvants to protect conidia and to maximise fungal performance . Extensive research showed that oil formulations are more efficacious than aqueous formulations or wettable powders under various temperature and moisture conditions . In our experiment, compared with wettable powders, oil‐based formulations of I. fumosorosea were more effective against P. xylostella at the same conidial concentrations.…”
Section: Discussionmentioning
confidence: 54%
“…78 Extensive research showed that oil formulations are more efficacious than aqueous formulations or wettable powders under various temperature and moisture conditions. 79,80 In our experiment, compared with wettable powders, oil-based formulations of I. fumosorosea were more effective against P. xylostella at the same conidial concentrations. Although the reason for the higher mortality induced by oil formulations is not known, it can be explained by the increased adherence of conidia on the cuticle.…”
Section: Discussionmentioning
confidence: 56%
“…Most studies on microbial control of ticks available report the performance of fungal formulations in bioassays held in optimal conditions of temperature and RH (Kaaya and Hassan, 2000;Maranga et al, 2005;Lopes et al, 2007;Fernandes and Bittencourt, 2008;Angelo et al, 2010;Camargo et al, 2012). The current study, however, reports the performance against the tick R. sanguineus of M. anisopliae formulated in oil or water, and exposed or not exposed to heat stress.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, oil extends the viability of conidia held at ambient conditions or under refrigeration (Prior et al, 1988). The positive effects of formulating entomopathogenic fungi in oil have been reported as, (a) increased fungus-induced mortality against cocoa weevil (Prior et al, 1988), triatomine bugs (Luz and Batagin, 2005), grasshoppers (Lomer et al, 2001) and whiteflies (Malsam et al, 2002); (b) increased ovicidal activity against Aedes aegypti mosquito (Albernaz et al, 2009) and Rhipicephalus annulatus tick (Samish et al, 2014), and (c) increased virulence against different life stages of the tick R. microplus (Angelo et al, 2010;Camargo et al, 2012).…”
Section: Rhipicephalus Microplusmentioning
confidence: 99%
“…Trials consisted of the topical administration of oil solutions, targeted against immature or adult stages [44]. The aim is to reduce the indiscriminate use of chemical acaricides, for avoiding contamination of food and environment, as well as the appearance of chemical resistance among tick populations [45].…”
Section: Entomopathological Agentsmentioning
confidence: 99%